A Glance at Congenital Heart Disease in Saudi Arabia - Albesher, Nour; M. Hassan, Sabah (Journal of King Abdulaziz University: Science, 2024)
Heart development is a complex process controlled by multiple genes (in interacting pathways), many of which remain unknown. Abnormal development of the heart results in a spectrum of congenital heart diseases (CHDs). These conditions may occur as isolated disorders or as part of a syndrome, with or without a family history, suggesting a genetic basis in some cases. A molecular understanding of heart development will help clinicians improve clinical diagnosis, provide accurate genetic counseling about recurrence risks, and potentially intervene in clinical care. In this review, we provide a glance at CHD in Saudi Arabia.